1979
DOI: 10.1126/science.204.4388.68
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Autotrophy: A Primary Source of Organic Carbon in Marine Sediments

Abstract: The chemoautotrophic fixation of carbon dioxide by bacteria is responsible for an appreciable component of the organic carbon in a sulfide-rich marine mud. A peak of carbon dioxide fixation (at 40 centimeters subbottom) coincides with peaks in the organic carbon content, the ratio of carbon to nitrogen, and bacterial cell counts. Stimulation of fixation by thiosulfate and inhibition by anaerobic conditions implicate the chemoautotrophic sulfur bacteria as primary producers in this environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…High rates of dark CO, assimilation have also been measured in the Black Sea (Sorokin 1964), the Saelenvann estuary (Indreba, et al IWgb), and the Cariaco Trench (Tuttle and Jannasch 1979). Kepkay et al (1979) found that chemoautotrophy may provide an appreciable source of organic matter in marine sediments, and bacterial chemoautotrophy may be the major source of primary productivity for deep-sea thermal vent communities (Jannasch and Wirsen 1979).…”
mentioning
confidence: 99%
“…High rates of dark CO, assimilation have also been measured in the Black Sea (Sorokin 1964), the Saelenvann estuary (Indreba, et al IWgb), and the Cariaco Trench (Tuttle and Jannasch 1979). Kepkay et al (1979) found that chemoautotrophy may provide an appreciable source of organic matter in marine sediments, and bacterial chemoautotrophy may be the major source of primary productivity for deep-sea thermal vent communities (Jannasch and Wirsen 1979).…”
mentioning
confidence: 99%
“…This coupling may also help explain the post-depositional persistence of organic matter in coastal sediments (e.g. Kepkay et al 1979, Rowe & Howarth 1985.…”
Section: Discussionmentioning
confidence: 99%
“…The sampling site used in this study was the area of Halifax Harbor known as Eastern Passage, which was also the site of previous studies (8,9,13,14,16 …”
Section: Methodsmentioning
confidence: 99%